Diabetic retinopathy and socioeconomic deprivation in Gloucestershire. - Scanlon, P; Carter, S; Foy, C; Husband, R; Abbas, J; Bachmann, M (2008)
OBJECTIVES: To investigate socioeconomic variations in diabetes prevalence, uptake of screening for diabetic retinopathy, and prevalence of diabetic retinopathy. METHODS: The County of Gloucestershire formed the setting of the study. A cross-sectional study of people with diabetes was done on a countywide retinopathy-screening database. Diabetes prevalence with odds ratios, uptake of screening, prevalence of any retinopathy and prevalence of sight-threatening retinopathy at screening were compared for different area deprivation quintiles. Logistic regression was used to adjust for confounding. RESULTS: With each increasing quintile of deprivation, diabetes prevalence increased (odds ratio 0.84), the probability of having been screened for diabetic retinopathy decreased (odds ratio 1.11), and the prevalence of sight-threatening diabetic retinopathy among screened patients increased (odds ratio of 0.98), while the prevalence of non-sight-threatening diabetic retinopathy remained unchanged with each increasing quintile of deprivation. CONCLUSION: Sight-threatening diabetic retinopathy was associated with socioeconomic deprivation, but non-sight-threatening diabetic retinopathy was not. Uptake of screening was inversely related to socioeconomic deprivation.